Efektivitas Efektivitas Aplikasi Sikancil (Sistem Informasi Kependudukan dan Pencatatan Sipil) Di Disdukcapil Kota Tanjungpinang - Muhammad Reza Saputra; Veronisa; Ezra Zuriel Roring; Pasaribu, Esteria (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2022)
Many organizations are enhancing the quality of their services in numerous ways as a result of the rapid growth of the information world and related technological advancements. The Population and Civil Registration Information System (Sikancil) application was released by the Department of Population and Civil Registration (Disdukcapil) Tanjungpinang. This study uses a descriptive research method with a qualitative approach to evaluate the services provided by the Sikancil Application System at the Department of Population and Civil Registration (Disdukcapil) Tanjungpinang. At the Tanjungpinang Disdukcapil office, data collection methods included interviews, observations, and related evaluation documentation. These methods were used in conjunction with the Sikancil application system. The collected data was then qualitatively analyzed, supported by the findings of the interviews, and in accordance with Dunn's evaluation approach, which suggested identifying alternative policy objectives in problem-solving that include effectiveness, efficiency, evaluation, responsiveness, and accuracy. the service evaluation theory approach, according to Dunn, suggests evaluating the usefulness of alternative policies in solving problems that include effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. the data obtained is then qualitatively analyzed by looking at all the data that has been collected and supported by the results of interviews.